1993
DOI: 10.1029/93jc02501
|View full text |Cite
|
Sign up to set email alerts
|

Variability of sources and sinks of CO2 in the western Indian and southern oceans during the year 1991

Abstract: we describe spatial and temporal variations of sea surface carbon dioxide fugacity (fCO2) in the Antarctic, Subantarctic, subtropical, and tropical regions of the Indian Ocean (including the Red Sea). The measurements were made continuously with an infrared technique during seven cruises. We study the temporal variations of fCO2 at daily, monthly and seasonal scales in selected areas. High-frequency variabilities of 20 gatm/d have been observed near polar frontal zone. Both spatial and temporal fCO2 variation•… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 49 publications
7
86
1
1
Order By: Relevance
“…It is also seen that pCO 2 sea varies largely in the SSIZ, but causes are ascribed to physical and biological processes. These results suggest that it is possible to reconstruct pCO 2 sea for the area north of PFZ using the observed temperature dependence of pCO 2 sea , but more sophisticated methods are required for the SSIZ, as suggested by Poisson et al [1993] and demonstrated by Metzl et al [1995].…”
Section: Resultsmentioning
confidence: 85%
“…It is also seen that pCO 2 sea varies largely in the SSIZ, but causes are ascribed to physical and biological processes. These results suggest that it is possible to reconstruct pCO 2 sea for the area north of PFZ using the observed temperature dependence of pCO 2 sea , but more sophisticated methods are required for the SSIZ, as suggested by Poisson et al [1993] and demonstrated by Metzl et al [1995].…”
Section: Resultsmentioning
confidence: 85%
“…Until now, 3 designs of equilibrators, or combination of them, are commonly used: the ''bubble Weiss type'' equilibrator, the ''laminary flow type'' equilibrator and the ''shower type'' equilibrator (Takahashi, 1961;Keeling et al, 1965;Kelley, 1970;Weiss, 1981;Copin-Montegut, 1985;Goyet et al, 1991;Schneider et al, 1992;Poisson et al, 1993;Roberston et al, 1993;Wanninkhof and Thoning, 1993;Goyet and Peltzer, 1994). Ko¨rtzinger et al (1996) have recently proposed a review of these equilibrators and have compared results obtained at sea using two different designs of ''bubble type'' equilibrators.…”
Section: Introductionmentioning
confidence: 99%
“…The surface C T concentrations are influenced by lateral and vertical mixing, photosynthesis, oxidation of organic matter and changes in temperature and salinity (Poisson et al, 1993;Takahashi et al, 1993). All these processes are directly or indirectly correlated with sea surface temperature (Lee et al, 2000).…”
Section: Fitting C T In the Mediterranean Sea Surface Watersmentioning
confidence: 99%